Gambaran Penggunaan Obat Antihipertensi di Apotek Rawat Jalan Rumah Sakit “X” Tarakan Tahun 2022 - Benyamin; Syuhada Syuhada; Benazir Evita Rukaya (Politeknik Kaltara, 2023)
Hypertension is a global health problem often encountered, and the appropriate use of antihypertensive drugs is very important for optimal blood pressure control. Therefore, it is necessary to research the description of the use of antihypertensive drugs in various health facilities. The purpose of this study was to describe the prescription of antihypertensive drugs in patients at